2016
DOI: 10.21147/j.issn.1000-9604.2016.05.01
|View full text |Cite
|
Sign up to set email alerts
|

Revalidation of a prognostic score model based on complete blood count for nasopharyngeal carcinoma through a prospective study

Abstract: ObjectiveIn our previous work, we incorporated complete blood count (CBC) into TNM stage to develop a new prognostic score model, which was validated to improve prediction efficiency of TNM stage for nasopharyngeal carcinoma (NPC). The purpose of this study was to revalidate the accuracy of the model, and its superiority to TNM stage, through data from a prospective study.MethodsCBC of 249 eligible patients from the 863 Program No. 2006AA02Z4B4 was evaluated. Prognostic index (PI) of each patient was calculate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 38 publications
0
5
0
Order By: Relevance
“…Nasopharyngeal carcinoma (NPC) originates from the epithelial cells covering the surface of nasopharynx (1), and it is a rare malignancy with an age-standardized incidence of <1/100,000 person-years, except in certain endemic regions such as South China (2,3). Due to anatomical complexity of NPC and its tendency to metastasize, radiotherapy instead of surgery is the main therapeutic modality (4,5). Since the advent of intensity-modulated radiation therapy (IMRT) and concurrent chemotherapy (CCT), the highest 5-year overall survival (OS) of NPC in the literature has now achieved 85.0% (6).…”
Section: Introductionmentioning
confidence: 99%
“…Nasopharyngeal carcinoma (NPC) originates from the epithelial cells covering the surface of nasopharynx (1), and it is a rare malignancy with an age-standardized incidence of <1/100,000 person-years, except in certain endemic regions such as South China (2,3). Due to anatomical complexity of NPC and its tendency to metastasize, radiotherapy instead of surgery is the main therapeutic modality (4,5). Since the advent of intensity-modulated radiation therapy (IMRT) and concurrent chemotherapy (CCT), the highest 5-year overall survival (OS) of NPC in the literature has now achieved 85.0% (6).…”
Section: Introductionmentioning
confidence: 99%
“…Among the 64 studies on non-TNM factors, 18 proposed parameters were identified. Prognostic factors with consistent support from multiple studies included EBV-DNA level ( Table 3 ), primary gross tumor volume (GTV) ( 63 , 72 74 , 76 , 78 81 ), nodal GTV ( Table 4 ) ( 74 , 75 , 77 , 81 ), neutrophil-lymphocyte ratio (NLR) ( Table 5 ) ( 83 , 85 , 91 , 92 , 97 ), C-reactive protein (CRP)/albumin ratio ( 83 , 89 , 98 ), anemia ( 84 , 87 , 96 ), platelet count ( 82 , 86 ), lactate dehydrogenase (LDH) ( 88 , 95 ), and SUV max of the primary tumor ( 99 101 , 103 , 108 , 111 , 113 ) and total lesion glycolysis (TLG) ( Table 6 ) ( 104 , 111 ).…”
Section: Resultsmentioning
confidence: 99%
“…In the 18 studies that were included, nine inflammatory/hematological markers were evaluated: the most frequently proposed marker (n = 5) is NLR ( 83 , 85 , 91 , 92 , 97 ), followed by anemia (n = 3) ( 84 , 87 , 96 ), LDH (n = 2) ( 88 , 95 ), platelet count (n = 2) ( 82 , 86 ), and the CRP/albumin ratio (n = 3) ( 83 , 89 , 98 ). Other proposals with limited supporting evidence included high-sensitivity CRP (hs-CRP; n = 1) ( 54 ), platelet distribution width (PDW) ( 86 ), prognostic nutrition index (PNI) and albumin/globulin ratio (AGR) (n = 1) ( 93 ), D-dimer (n = 1) ( 94 ), and tumor-infiltrating lymphocytes (TIL; n = 1) ( 90 ).…”
Section: Discussionmentioning
confidence: 99%
“…In general, inflammatory cells could enhance the proliferating and metastatic abilities of tumor cells. Therefore, the elevated level of inflammatory cells might affect prognosis adversely [6,10].…”
Section: Discussionmentioning
confidence: 99%
“…It is chosen because it is fast, inexpensive, and has a practical functional index. Moreover, the CBC could reflect the biological characteristics of tumor cells indirectly and combining it with the TNM stage is very useful for building a more accurate predicting system of NPC patients' individualized outcomes [6]. However, there has been no study regarding the effect of radiotherapy on the CBC parameter.…”
Section: Introductionmentioning
confidence: 99%